Ethylene polymerisation with zirconocene supported in Al-modified MCM-41: catalytic behaviour and polymer properties - Campos, João M. (2013)
Heterogeneous olefin polymerisation catalysts were prepared by combining zirconocene with a series of purely siliceous and Al-containingMCM- 41 supports with different Si/Al ratios, using simplified and improved versions of the well-known direct impregnation and “MAO pre-treatment” methods. The catalysts were tested in ethylene polymerisation. Analysis of polymerisation activities and kinetic profiles led to a rationalisation on the effect of support Si/Al ratios and methods used for catalyst preparation over the catalytic behaviour for ethylene polymerisations. Polymers were characterised by scanning electron microscopy and differential scanning calorimetry. A mechanism is proposed to associate the formation or absence of fibrous morphology with polymerisation activities.